Arrhythmias and electrophysiology: The State of the Nation - Okreglicki, A (SA Heart Journal, 2017)
For far too long in South Africa, cardiac electrophysiology and an interest in arrhythmias has been treated like an orphaned infant of a distant relative, only to be tolerated in the home of cardiology where cardiac intervention, understood mainly as “plumbing”, is considered to be the favored son and heir. Yet, elsewhere, the fi eld of arrhythmias and cardiac electrophysiology (EP) has grown exponentially, arrhythmia and heart rhythm societies have passed their coming of age and EP is a recognized and certifi able subspecialty of cardiology. It is time, therefore, that EP, the “cardiac-electrician” son, be accepted and be accorded due respect, nurturing and equal opportunity in the South African family of cardiology.